Situation Report: Poland, 28 July 1989 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Jaruzelski Declares His Candidacy on Eve of Presidential Election / by Louisa Vinton Jaruzelski's One-Vote Victory / by Louisa Vinton Poland and the Vatican Re-establish Diplomatic Relations / by Anna Swidlicka The Polish Center for Public Opinion Research under Attack / by Roman Stefanowski Death of Kazimierz Sabbat, Poland's President in Exile / by Roman Stefanowski